Mark of the grizzly : revised and updated with more stories of recent bear attacks and the hard lessons learned - McMillion, Scott, 1956- (Lyons Press, 2012)
"Mark of the Grizzly relies on neither myth nor legend. Rather, it relies on the true accounts of dozens of attacks, from Yellowstone National Park to Alaska, from 1977 to 2010. Author Scott McMillion examines each attack and its aftermath, interviewing victims, survivors, and investigators. Hikers, photographers, hunters, scientists, and others tell their stories here, offering what they have learned and the lessons that others should know."--P. [4] of cover.